(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Post-viral pulmonary fibrosis in children has recently gained attention as a significant long-term complication of severe viral pneumonias, including those caused by respiratory syncytial virus, influenza, adenoviruses, and SARS-CoV-2. Recent studies (2022–2025) demonstrate that persistent alveolar injury, immune dysregulation, and aberrant repair mechanisms contribute to fibrotic remodeling in the pediatric lung, potentially leading to chronic respiratory impairment. Early diagnosis remains challenging due to overlapping radiological features between post-inflammatory changes and evolving fibrosis. High-resolution computed tomography and advanced imaging modalities, such as functional lung MRI, are emerging tools for early detection. Current therapeutic approaches include systemic corticosteroids, pulmonary rehabilitation, and supportive care, whereas antifibrotic drugs such as nintedanib are under clinical investigation in children. Preventive strategies, including vaccination, early antiviral therapy, and lung-protective ventilation in acute stages, play a crucial role in reducing the risk of fibrotic progression. Novel therapies—such as mesenchymal stem cell transplantation, targeted biologics, and small-molecule antifibrotic agents—are being explored in translational studies. This article reviews recent evidence on management and prevention strategies for pediatric post-viral pulmonary fibrosis and highlights future perspectives aimed at improving long-term outcomes.